Network Security Analysis and Bandwidth Management - Bagus Aji Saputro (International Journal of Science, Engineering, and Information Technology, 2021)
Computer network users have to spend a lot of money to use the Internet. The Internet has given a very big change in the dissemination of information, so that many people are using data through the Internet. This problem can be solved by MikroTik as a regulator of Internet data traffic and limiting bandwidth that can interfere with computer network activities in accordance with the regulations that have been applied. As a result of not being limited in bandwidth, it causes an overload on a network which has an impact on disrupting internet traffic on that network. Each agency should implement bandwidth restrictions according to the needs of users using the internet. Result from this research is not being limited in bandwidth, it causes an overload on a network which has an impact on disrupting internet traffic on that network. Each agency should implement bandwidth restrictions according to the needs of users using the internet.